Strategi Membangun Kedisiplinan pada Anak Usia Dini Melalui Bamainan: Studi Budaya Masyarakat Banjar di Kalimantan Selatan - Faqihatuddiniyah, Faqihatuddiniyah; Nurdin, Encep Syarief; Mariani, Naniek; Kosasih, Aceng (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
This study investigates strategies for fostering discipline in early childhood within the Banjar community by integrating traditional games (bamainan) as a cultural medium. The research highlights the habituation method as a key approach, whereby teachers establish routines such as arriving on time, tidying up after play, queuing for turns, and maintaining classroom order. This process is enhanced through motivational storytelling, consistent teacher modeling, and the moral guidance of acceptable behavior, contributing to the holistic development of discipline in young learners.The methodology employed a qualitative descriptive approach, focusing on cultural practices in Banjar society. Data collection techniques included interviews, observations, and documentation to explore how discipline strategies are implemented in early childhood education settings. The analysis involved multiple stages: data collection, reduction, presentation, and conclusion drawing. The study also examined supporting and inhibiting factors influencing the development of discipline, such as teacher consistency, parental collaboration, and the child’s developmental readiness.The findings reveal that discipline-building in early childhood is deeply rooted in the cultural values of the Banjar community. Teachers play a pivotal role as models, demonstrating behaviors and engaging in active participation during activities to instill good habits. Supporting factors include the synergy between teachers and parents, while challenges arise from inconsistent parental involvement and the varying developmental stages of children. This research underscores the importance of culturally contextualized methods in nurturing character and discipline in early childhood education.